2020
DOI: 10.1038/s41598-020-77338-x
|View full text |Cite
|
Sign up to set email alerts
|

Mislabelling and high mercury content hampers the efforts of market-based seafood initiatives in Peru

Abstract: Peru is experiencing a “gastronomic boom” that is increasing the demand for seafood. We investigated two implicit assumptions of two popular sustainable seafood consumer-based initiatives: (1) seafood is labelled correctly, and (2) the recommended species are healthy for consumers. We used DNA barcoding to determine the taxonomic identity of 449 seafood samples from markets and restaurants and analysed the concentration of total mercury (THg) in a sub-sample (271 samples) of these. We found that a third of sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…The food products offered vary from fresh food to healthier processed foods [9]. Seafood culinary business can be sustainable by properly labeling and selecting types of marine fish that can be recommended as healthy food for consumers [10]. Product design driven by the COVID-19 pandemic conditions gave birth to new, more varied products.…”
Section: Fig 4 Identity Of Respondentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The food products offered vary from fresh food to healthier processed foods [9]. Seafood culinary business can be sustainable by properly labeling and selecting types of marine fish that can be recommended as healthy food for consumers [10]. Product design driven by the COVID-19 pandemic conditions gave birth to new, more varied products.…”
Section: Fig 4 Identity Of Respondentsmentioning
confidence: 99%
“…A third of seafood was mislabeled and more than a quarter of the samples had mercury levels above the US EPA recommended limit (300 ng/g ww). In addition, 30% of the samples are threatened and protected species [10]. In this study, the atmosphere change variable is a variable that has no significant effect on product diversification.…”
mentioning
confidence: 90%
“…In Peru, shark meat is found in markets labeled interchangeably as tiburón ("shark") or tollo. Tollo is an all-encompassing term referring to some species of sharks of the families Carcharhinidae, Scyliorhinidae, Squalidae, and Triakidae (Biffi et al, 2020). A study conducted along the Peruvian coast found that 72% of people surveyed had consumed tollo, however, only 20% of those reported eating shark meat (Lopez de la .…”
Section: Introductionmentioning
confidence: 99%
“…The Peruvian sea is home to at least 67 shark species (Cornejo et al 2015;Kelez et al 2020), half of which interact with Peruvian SSFs (Gonzalez-Pestana et al 2016). Currently, six Mustelus species occur in Peruvian waters: M. californicus, M.…”
mentioning
confidence: 99%
“…On the other hand, the sicklefin smooth-hound M. lunulatus has never been reported to species-level in Peruvian landing records, despite being listed as a commercial species by IMARPE in the '90s decade (Elliot-Rodriguez et al 1996). Furthermore, two independent molecular studies found M. lunulatus in retail markets and supermarkets from Lima and Tumbes (Marín et al 2018;Biffi et al 2020). Mustelus species are traded in domestic markets simply as tollos (López de la Lama et al 2018).…”
mentioning
confidence: 99%